Survivin Clinical Features in Cervical Cancer - Miftakh Nur Rahman; Chyntia Resti Wijaya; Maria Novalentina (Molecular and Cellular Biomedical Sciences, 2017)
Cervical cancer is the primary lethal malignancy for women worldwide, but because it develops over time, it would be one of the most preventable types of cancer. Dysregulation of apoptosis in cells plays a critical role in the malignancy development. Survivin is the smallest inhibitor apoptotic protein (IAP) which has an important part in regulating cell division and inhibitor of apoptosis. This review focused on survivin features in cervical cancer from mechanisms of malignancy relationship to human papillomavirus (HPV) infection through E6 oncogenic protein, role as a biomarker in diagnosis, prognosis, staging and prediction of metastasis, and also as a target for therapy. Regulation of survivin divided into two main groups; cell cycle dependent and cell cycle independent pathway to maintain life and death balance. Survivin expression is upregulated by E6 protein simultaneously repressing p53. Thus cancerous cervical tissue developed. Survivin is also upregulated in hypoxia, a common condition in many tumors and increased angiogenesis. Survivin plays a major role in chemotherapy and radiation resistance in many cases of cervical cancer. As a target of therapy, survivin has a promising performance, suggested very specific and no issue of resistance and also reducing resistance to chemo and radiation therapy. The goal of treatment is to lower survivin expression through transcription inhibition, immunotherapy based on cytotoxic T cell (CTL) activity and gene therapy.  Keywords: cervical cancer, survivin, HPV E6 oncoprotein, therapy